Lagrangian detection of moisture sources for the Southern Patagonia Icefield - Langhamer, Lukas (2017)
The moisture source of the Southern Patagonia Icefield (SPI) and its transport is not yet fully understood. It has a large impact on the stable isotope composition of the SPI, adjacent lakes and nearby vegetation, and is hard to quantify from observations. This study detects the moisture sources of the SPI with a Lagrangian moisture source method. The kinematic 18-day backward trajectory calculations use reanalysis data from the European Centre for Medium-Range Weather Forecasts (ERA-Interim) from January 1979 to January 2017. The dominant moisture sources are found in the South Pacific Ocean between 80 °W to 160 °W and 30 °S to 60 °S. Most of the moisture travels less than 10 days to reach the SPI. The majority of the trajectories originate from above the boundary layer but enter the Pacific boundary layer to reach the maximum moisture uptake 2 days before arrival. During the last day the trajectory rise as they encounter to topography. A persistent anticyclonic flow in the subtropics and advection of moist air by the prevailing westerlies are the principal moisture transport mechanisms. Seasonal and El-Niño Southern Oscillation (ENSO) related moisture source variabilities are found. In austral winter months, more moisture originates from the subtropics. Summer and La-Niña months show enhanced moisture uptake in the mid-latitudes. Opposite behavior is exhibited by El-Niño months. The ENSO related moisture source anomalies are half as large as the seasonal anomalies. Both phases have similar seasonal occurrence. In general, heavy precipitation months indicate more long-range transport and a strengthening of the westerlies with enhanced moisture uptake in the mid-latitudes. By contrast the westerly wind belt shifts poleward during low precipitation months. Their anomalies show enhanced moisture transport from the south-east South Atlantic and moisture recycling at southernmost South America. by Lukas Langhamer Masterarbeit University of Innsbruck 2017